A new shrimp species of the genus Lebbeus White, 1847 (Crustacea: Deacpoda: Caridea: Thoridae) from a deep-sea cold seep site off southwestern Taiwan - Chan, Tin-Yam; Komai, Tomoyuki (Zootaxa, 2017)
A new species of the thorid shrimp genus Lebbeus White, 1847 is reported upon from a deep-sea cold seep site off southwestern Taiwan. The new species belongs to the group characterized by the possession of epipod only on maxilliped III and pereiopod I, and appears closest to L. curvirostris Zarenkov, 1976, known only from off Peru, Eastern Pacific and L. manus Komai & Collins, 2009 from the Manus Basin, Bismarck Sea, Southwest Pacific. It differs from the latter two species in having a larger supraorbital tooth and more numerous spines on the meri of the pereiopods III to V. The present new species is the fifth of the genus known from waters around Taiwan.